Trisomy 14 as a Sole Chromosome Abnormality Is Associated with Older Age, a Heterogenous Group of Myeloid Neoplasms with Dysplasia, and a Wide Spectrum of Disease Progression. (20th January 2011) - Cui, Wei; Bueso-Ramos, Carlos E.; Yin, C. Cameron; Sun, Jianlan; Chen, Su; Muddasani, Ramya; Lu, Gary
Abstract : Trisomy 14 is a rare recurrent cytogenetic abnormality in myeloid neoplasms; however, its clinicopathologic features have not been well described. We report the clinicopathologic, immunophenotypic, and molecular genetic features of 16 cases of myeloid neoplasms with isolated trisomy 14. Our results show that cases with isolated trisomy 14 encompass a heterogenous group of myeloid neoplasms including myelodysplastic syndrome (MDS, 44%), myelodysplastic/myeloproliferative neoplasms (31%), and acute myeloid leukemia (25%). The patients are usually elder (median age 71 years), and there is a male predominance (82%). Multilineage dysplasia is noted in all cases. Oncogenic mutations of genes involved in cell proliferation and/or survival rarely occur. Compared with cases of MDS with diploid karyotype, patients of MDS with isolated trisomy 14 demonstrate a similar overall survival and rate of leukemia transformation.